Peran Desain Kerja dalam Meningkatkan Produktivitas SDM - Dwi Ariningsih; Untung Lasiyono (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Work design is a crucial human resource (HR) management element that directly affects organizational productivity. This research examines how aspects of work design, including physical arrangements, task division, team interaction, and organizational culture, can influence employee motivation and performance. With the right approach, work design creates a comfortable and supportive environment and encourages collaboration and innovation. Through an analysis of best practices in work design, this article identifies strategies organizations can implement to improve HR productivity and the long-term implications for business success. The results of this study show that the role of work design is crucial in improving HR productivity. Implementation of appropriate and good work design will increase the productivity of appropriate human resources to achieve the goals desired by the company or organization.